Upaya Meningkatkan Keaktifan Belajar Siswa melalui Model Pembelajaran Project Base Learning di SMA Negeri 4 Bojonegoro - Darmisih Darmisih; Edy Siswanto; Albrian Fiky Prakoso (ISLAMIKA, 2023)
This study aims to increase the active learning of SMA Negeri 4 Bojonegoro students through project base learning. This research is included in the type of classroom action research which includes several cycles. Each cycle includes planning, implementing actions, observing, and reflecting. The subjects of this study were students of class X-1 at SMA Negeri 4 Bojonegoro consisting of 33 students. The research instruments were observation sheets, questionnaires and documentary evidence. Data collection techniques through observation, questionnaires and documentation studies. Data analysis techniques in this study include data reduction, data selection, data simplification, and conversion of raw data from field notes. Based on the results of pre-cycle observations of student activity by 48% in the "very less" category and after implementing project-based learning in cycle I, the percentage of student activity became 65% in the "enough" category, and increased in the results of observations in cycle II which showed a percentage of 81%. into the "good" category. The results of giving a questionnaire in the pre-cycle were 3.22 with the "enough" category after implementing project-based learning in cycle I, the student response score was 3.78 with the "active" category. After the second cycle of action, the score for student learning activity increased to 4.65 in the "very active" category. Based on the research results, the Project Based Learning learning model can increase student activity in learning.